Evolution of viral variants in remdesivir‐treated and untreated SARS‐CoV‐2‐infected pediatrics patients. Issue 1 (4th September 2021) - Boshier, Florencia A. T.; Pang, Juanita; Penner, Justin; Parker, Matthew; Alders, Nele; Bamford, Alasdair; Grandjean, Louis; Grunewald, Stephanie; Hatcher, James; Best, Timothy; Dalton, Caroline; Bynoe, Patricia Dyal; et al.
Abstract: Detailed information on intrahost viral evolution in SARS‐CoV‐2 with and without treatment is limited. Sequential viral loads and deep sequencing of SARS‐CoV‐2 from the upper respiratory tract of nine hospitalized children, three of whom were treated with remdesivir, revealed that remdesivir treatment suppressed viral load in one patient but not in a second infected with an identical strain without any evidence of drug resistance found. Reduced levels of subgenomic RNA during treatment of the second patient, suggest an additional effect of remdesivir on viral replication. Haplotype reconstruction uncovered persistent SARS‐CoV‐2 variant genotypes in four patients. These likely arose from within‐host evolution, although superinfection cannot be excluded in one case. Although our dataset is small, observed sample‐to‐sample heterogeneity in variant frequencies across four of nine patients suggests the presence of discrete viral populations in the lung with incomplete population sampling in diagnostic swabs. Such compartmentalization could compromise the penetration of remdesivir into the lung, limiting the drugs in vivo efficacy, as has been observed in other lung infections.